Induced breeding of endangered striped dwarf Catfish (Mystus vittatus) and its embryonic and larval development (Research in Agriculture Livestock and Fisheries, 2015)
The present study reports successful induced breeding of endangered striped dwarf catfish Mystus vittatus and its different embryonic and larval developmental stages. Three different doses of PG were tested, viz. 17, 15 and 13 mg PG/kg body weight for female and 14, 12 and 10 mg PG/kg body weight for male with maintaining (1:1) male and female ratio. The hormone doses 13 mg/kg for female and 10 mg/kg for male provided the best result i.e. 91.33±2.08% fertilization and 85.00±2% hatching rates. Mean survival percentage of the spawns up to 21 days was 8.00±1%. The fertilized eggs were found to be transparent, demersal, spherical, adhesive and brownish in colour and first cleavage took place within 35-40 min post-fertilization at 29.56± 0.25oC. Hatching took place at 24 h. after fertilization. Newly hatched larvae were 3-4 mm in length and slender, transparent and the yolk sac oval in shape. Anus was situated at almost mid ventrally. Larvae started to feed at 48-72 h post-hatching. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22376 Res. Agric., Livest. Fish.1(1): 127-136, Dec 2014